Bell Pottinger And The Dark Art Of Public Relations - Sonja Verwey; Clarissa Muir (Communicare)
The spurious and unethical actions of the renowned global public relations (PR) firm Bell Pottinger in early 2017 cast a dark cloud over the PR industry in general. Aside from the economic and sociopolitical ramifications that emerged in the wake of this scandal, it has tainted the moral standing of all public relations professionals, including those in South Africa. There is little doubt that tactics such as offering to manipulate a client’s online reputation through the use of fake online accounts, newly created blog pages or fake online reviews are unethical, and take the industry back to a less glorious time in its history at a point when much emphasis is being placed on both ethics and values-based practice globally. Moral philosophy provides a basis for rationalising human motivation in decision making and action. However, it can be argued that there is potentially a mismatch between theories and moral frameworks created for individualistic cultures, and their application within communal cultures. Building social capital in any society begins with a commitment to support the collective interests of the community. Thus, any discussion of the value of ethical communication practice for society must begin with a concern for the nature and integrity of community. Against this background this article utilises the Bell Pottinger case study to examine the tensions that arise between individual values and communal PR practice, and to explore the moral implications of ethical PR practice in a communal context such as South Africa.